Stable osteosynthesis of pathological fracture of long bones in patients with multiple myeloma; retrospective evaluation of the therapy - Krtička, Milan; Chovanec, Martin; Smékal, Pavel; Štork, Martin; Pour, Luděk (Úrazová chirurgie, 2020)
Objective: Retrospective evaluation of the results of operating treatment in patients with multiple myeloma (MM) with pathological fracture of the long bone treated by the stable osteosynthesis (OS) at the Trauma Clinic of the University Hospital Brno in the period from January 2013 to December 2018. Material and methods: Retrospective evaluation of the set of 410 patients treated with MM at the University Hospital Brno in the period of 2013–2018. Both inclusion and exclusion criteria were determined. The method of the performed osteosynthesis of a pathological fracture of the long bone depended on its localisation. It was either a nailing or plating osteosynthesis with stabilisation using the Prevotʼs rods. The following was evaluated on the acquired set of patients. Epidemiology data, fracture occurrence mechanism and type of fracture, intensity of pain, Mirels´ score, type of the osteosynthesis used, time section from determination of the MM diagnosis to occurrence of the fracture and also from the performed osteosynthesis to the healing of the fracture, and any treatment complications, if appropriate. Results: Following the satisfaction of the inclusion and exclusion criteria, a set was formed of 24 patients with MM, who suffered a total of 32 pathological fractures of long bones in the myeloma deposits and were treated using the osteosynthesis method. 11 men and 13 women were represented in the set. The average age of the monitored patients was 71 years. Fractures were localized in 20 cases into the region of diaphysis and proximal humerus, once into the radial area, and in 11 cases into the femoral area. Nailing osteosynthesis was used in 26 fractures (82 %), plating osteosynthesis was used in 5 fractures (15 %), and Prevotʼs rods were used in 1 case (3 %). In correlation with the used osteosynthesis method, we reported the healing of the fracture with a bony callus in 29 cases (91 %), in 2 cases (6 %) the direct healing, and 1 fracture did not heal and a false joint was formed (3 %). The following complications occurred during the treatment in 23 patients: periimplant fracture (N=2), and proximalisation of humeral nail with interference into subacromial space (N=1). Conclusion: MM represents a serious hematologic disease. Unlike in metastatic affection of bones with solid tumours, performance of stable osteosynthesis is indicated in respect of myeloma bone disease in the case of a pathological fracture of long bones, which does not exclude simultaneous systemic treatment of MM or radiotherapy.
Keywords: Multiple Myeloma; fraktury spontánní; mnohočetný myelom; Fracture Fixation, Internal; vnitřní fixace fraktury; Aged; Fractures, Spontaneous; retrospektivní studie; Bone and Bones; Humans; výsledek terapie; kosti a kostní tkáň; senioři; lidé; Middle Aged; lidé středního věku; Retrospective Studies; Treatment Outcome